2023
DOI: 10.1039/d3ta01918g
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of cobalt fluoride (CoF2)/multi-walled carbon nanotube (MWCNT) nanocomposites and improvement of their electrochemical performance as cathode materials for Li-ion batteries

Abstract: Conversion-type metal fluoride cathodes are considered promising candidates for electrochemical applications owing to their large specific capacities and high operating voltages. However, harnessing the potentially high energy-density of metal fluorides...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
(90 reference statements)
0
0
0
Order By: Relevance
“…For the Co 2p peak (Figure B,D,F), across different samples, the primary signal after deconvolution, at energies of 781.2 eV (10 mM CoF 2 ), 781.8 eV (30 mM CoF 2 ), and 781.6 eV (100 mM CoF 2 ), could be attributed to the Co 2+ state. , Another notable peak at higher binding energies, above 783.0 eV, is related to the presence of Co–F bonds, identifiable as cobalt fluoride (CoF 2 ) . This interpretation is further supported by the main fluorine signal F 1s (Figure C,E,G) which displayed a maximum binding energy ranging from about 684.0 eV (100 mM) to about 687.5 eV (10 mM), confirming the presence of cobalt fluoride in the materials. Similar to the findings of the EDS study (Figure F,G,H), an increase in the Co concentration was observed in correlation with the variation in the amount of CoF 2 added to the electrolyte. The Co content in the oxide layer ranged from 0.2 atom % (10 mM) to 0.3 atom % (100 mM).…”
Section: Resultsmentioning
confidence: 68%
“…For the Co 2p peak (Figure B,D,F), across different samples, the primary signal after deconvolution, at energies of 781.2 eV (10 mM CoF 2 ), 781.8 eV (30 mM CoF 2 ), and 781.6 eV (100 mM CoF 2 ), could be attributed to the Co 2+ state. , Another notable peak at higher binding energies, above 783.0 eV, is related to the presence of Co–F bonds, identifiable as cobalt fluoride (CoF 2 ) . This interpretation is further supported by the main fluorine signal F 1s (Figure C,E,G) which displayed a maximum binding energy ranging from about 684.0 eV (100 mM) to about 687.5 eV (10 mM), confirming the presence of cobalt fluoride in the materials. Similar to the findings of the EDS study (Figure F,G,H), an increase in the Co concentration was observed in correlation with the variation in the amount of CoF 2 added to the electrolyte. The Co content in the oxide layer ranged from 0.2 atom % (10 mM) to 0.3 atom % (100 mM).…”
Section: Resultsmentioning
confidence: 68%